A Case Series of Parechovirus Encephalopathy: Apnea and Autonomic Dysregulation in Critically Ill Infants. (October 2018) - Ristagno, Elizabeth H.; Bhalla, Sonam C.; Rasmussen, Lindsey K.
This article aims to describe a rare cause of severe encephalitis in 2 cases of infants with signs of intracranial hypertension and severe autonomic dysregulation. The authors conclude that human parechoviruses are becoming a more recognized cause of encephalitis because of the increasing use of rapid detection methods. With early recognition of this clinical entity, improved care can be administered.